Analysis of Energy Sharing Impacts in a Commercial Community: A Case of Battery Energy Storage System Deployment for Load Leveling - Li, You; Wang, Yafei; Fukuda, Hiroatsu; Gao, Weijun; Qian, Fanyue (Frontiers in Energy Research, 2022)
The energy use between the day and night has been a key point to make good use of utilities. As one of solutions, the energy storage system becomes more attractive to level the grid load and has been introduced independently into many communities with a high cost. There is a possibility to integrate the independent energy storage system to efficiently save the money and improve the energy use. called “battery sharing”. It highlights the interaction between a smart grid, smart buildings and distributed energy storage to achieve better energy management practices. In this paper, we provide a potential analysis method of battery sharing by establishing a coordinated control model of distributed battery system. As a case study, we selected 39 buildings with a different capacity of energy storage system as battery sharing community, to optimize sharing schedules and the load leveling performance. The results have shown that battery sharing could achieve the 13.2% reduction of the building battery capacity compared with independent operation. We further investigate the impact of building’s load profile patterns on the battery capacity in battery sharing community. It has shown that it is very effective in economics to introduce a larger capacity of battery system into the buildings with higher electricity consumption without rest day through the year. The optimal BESS capacity in commercial buildings depends on the lowest daytime power consumption. Among them, commercial buildings with closing days have limitations on BESS deployment. On closing days, buildings can only use BESS by sharing. Buildings with two closing days on one week lose 14.3% more energy than those with one day.